2021
DOI: 10.1007/s13577-021-00624-x
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsies in epilepsy: biomarkers for etiology, diagnosis, prognosis, and therapeutics

Abstract: Epilepsy is one of the most common diseases of the central nervous system, impacting nearly 50 million people around the world. Heterogeneous in nature, epilepsy presents in children and adults alike. Currently, surgery is one treatment approach that can completely cure epilepsy. However, not all individuals are eligible for surgical procedures or have successful outcomes. In addition to surgical approaches, antiepileptic drugs (AEDs) have also allowed individuals with epilepsy to achieve freedom from seizures… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…In our study, the proportion of patients with epilepsy with a poor prognosis was 35.42%. Previous research results showed that the proportion of patients with epilepsy with a poor prognosis was about 10% [ 15 17 ]. There is such a difference, which may be because we only target refractory epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the proportion of patients with epilepsy with a poor prognosis was 35.42%. Previous research results showed that the proportion of patients with epilepsy with a poor prognosis was about 10% [ 15 17 ]. There is such a difference, which may be because we only target refractory epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Missing are reports of increasing concentrations of an inflammation indicator preceding a seizure 121 . Without this type of information everything presented here is rather indirect support for the putative benefits of a closed‐loop system.…”
Section: Timingmentioning
confidence: 88%
“…Among the more interesting candidates are microRNA (miRNA) 120 , 121 , 122 , 123 and circular RNA (circRNA), 124 , 125 which can play a prominent role in regulating the immune system. 121 , 126 , 127 In vivo measurement capabilities are not yet available.…”
Section: Measurement Of Inflammation—what To Measure?mentioning
confidence: 99%
“…Similarly, once a treatment is initiated, it is hard to follow up certain patients who cannot report their seizure frequency due to intellectual disability, the presence of solely nocturnal seizures, or focal seizures with impaired consciousness and amnesia. 1,[5][6][7] All of these arguments demonstrate the value that a good (fluid) biomarker could offer.…”
Section: Introductionmentioning
confidence: 97%
“…However, the main aim of these tests is the exclusion of other pathologies, lacking a representative fluid biomarker for epileptogenesis, seizures, or status epilepticus (SE). Similarly, once a treatment is initiated, it is hard to follow up certain patients who cannot report their seizure frequency due to intellectual disability, the presence of solely nocturnal seizures, or focal seizures with impaired consciousness and amnesia 1,5–7 . All of these arguments demonstrate the value that a good (fluid) biomarker could offer.…”
Section: Introductionmentioning
confidence: 99%